Unveiling The Fiqh Treasures: Kitab Sabilal Muhtadin By Sheikh Muhammad Arsyad Al-Banjari - Ruslan, Ruslan; Mahmud, Hamdan; Rusdiyah; Naimah; Mohd Hatta Hani (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2023)
This research deeply explores the interpretation of fiqh verses in the book 'Sabilal Muhtadin' authored by Sheikh Muhammad Arsyad al-Banjari and its connection to the Banjar community. The book, an extensive exploration of the Syafii school of thought, intricately weaves together fiqh, hadith, and Qur'anic interpretation. Analyzing over 184 traditions across two volumes, al-Banjari not only references renowned scholars but also introduces independent perspectives on Islamic law. His method of interpreting legal verses, incorporating vocabulary analysis and Prophet Traditions, showcases a comprehensive understanding deeply rooted in scholarly tradition. Moreover, this research highlights the fusion of various interpretative styles within Sabilal Muhtadin, positioning it as an amalgamation of textual evidence and reasoned analysis—a unique contribution to the realm of Islamic jurisprudence. The category of tafsir is characterized by fiqhi and the method is divided into three; tafsir with history, tafsir with ra'yu (linguistic analysis, kias and logical reasoning), and combined tafsir (idzdiwaji).